2012
DOI: 10.1051/0004-6361/201118395
|View full text |Cite
|
Sign up to set email alerts
|

Accretion dynamics in the classical T Tauri star V2129 Ophiuchi

Abstract: Context. Classical T Tauri stars are variable objects on several timescales, but just a few of them have been studied in detail, with different observational techniques and over many rotational cycles to enable the analysis of the stellar and circumstellar variations on rotational timescales. Aims. We test the dynamical predictions of the magnetospheric accretion model with synoptic data of the classical T Tauri star V2129 Oph obtained over several rotational cycles. Methods. We analyze high resolution observa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
111
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(122 citation statements)
references
References 40 publications
11
111
0
Order By: Relevance
“…The spectrum in several Hydrogen lines was calculated and compared with observed spectra. A good match was obtained between the modeled and observed spectra [81].…”
Section: Variabilitysupporting
confidence: 64%
See 1 more Smart Citation
“…The spectrum in several Hydrogen lines was calculated and compared with observed spectra. A good match was obtained between the modeled and observed spectra [81].…”
Section: Variabilitysupporting
confidence: 64%
“…They have shown that conical winds may explain different features in the hydrogen spectral lines, in the He I line and also a relatively narrow, low-velocity blueshifted absorption components in the He I λ10830 which is often seen in observations [79]. Further, the 3D MHD+3D radiative transfer codes have been used to model the young star V2129 Oph, where the parameters of the star including the surface magnetic field distribution are known [81]. The spectrum in several Hydrogen lines was calculated and compared with observed spectra.…”
Section: Variabilitymentioning
confidence: 99%
“…The HeI (5876 Å) line also comes from the shock region and its radial velocity variability is due to the rotation of the hot spot with respect to our line of sight. The prediction of hot spot filling factor and location from the ZDI results was confirmed through the modeling of both veiling variability and HeI (5876 Å) line radial velocity variations [2].…”
Section: V2129 Ophmentioning
confidence: 64%
“…A multiwavelength observing campaign of this system was organized in 2009, which included simultaneous optical and near-IR photometry, high resolution spectroscopy and spectropolarimetry, and Chandra X-ray observations [2,3,18].…”
Section: V2129 Ophmentioning
confidence: 99%
“…More recently, a time-variable spectrum in hydrogen lines has been calculated from the 3D MHD model of V2129 and has been compared with the time-variable spectrum obtained from the observations of this star [44]. Comparisons show a good match between the observed and modeled spectra.…”
Section: Accretion To Stars With Complex Magnetic Fieldmentioning
confidence: 99%